Hydrophilicity and carbon chain length effects on the gas sensing properties of chemoresistive, self-assembled monolayer carbon nanotube sensors - Juan Casanova-Cháfer; Carla Bittencourt; Eduard Llobet (Beilstein Journal of Nanotechnology, 2019)
Here we describe the development of chemoresistive sensors employing oxygen-plasma-treated, Au-decorated multiwall carbon nanotubes (MWCNTs) functionalized with self-assembled monolayers (SAMs) of thiols. For the first time, the effects of the length of the carbon chain and its hydrophilicity on the gas sensing properties of SAMs formed on carbon nanotubes are studied, and additionally, the gas sensing mechanisms are discussed. Four thiols differing in the length of the carbon chain and in the hydrophobic or hydrophilic nature of the head functional group are studied. Transmission electron microscopy, Raman spectroscopy and X-ray photoelectron spectroscopy are used to analyze the resulting gas-sensitive hybrid films. Among the different nanomaterials tested, short-chain thiols having a hydrophilic head group, self-assembled onto Au-decorated carbon nanotubes were most responsive to nitrogen dioxide and ethanol vapors, even in the presence of ambient humidity. In particular, this nanomaterial was about eight times more sensitive to nitrogen dioxide than bare Au-decorated carbon nanotubes when operated at room temperature. This response enhancement is attributed to the interaction, via strong hydrogen bonding, of the polar molecules tested to the polar surface of hydrophilic thiols. The approach discussed here could be extended further by combining hydrophilic and hydrophobic thiol SAMs in Au-MWCNT sensor arrays as a helpful strategy for tuning sensor response and selectivity. This would make the detection of polar and nonpolar gas species employing low-power gas sensors easier, even under fluctuating ambient moisture conditions.